Rolling Back Russia's Spatial Disparities : Re-assembling the Soviet Jigsaw Under a Market Economy - World Bank (Washington, DC: World Bank, 2018)
Russia’s spatial disparities stem largely from its economic geography, which is unique and has no parallels even when compared to seemingly similar countries such as Australia and Canada. While Australia and Canada also have large land masses and even lower population densities than Russia, a large share of their populations live near the border or the sea. In contrast, Russia’s people are more dispersed inland. Moreover, the populations of Australia and Canada are concentrated in major cities: more than two-thirds of their populations live in the three largest urban centers. On the other hand, Moscow, St. Petersburg, and Nizhny Novgorod are home to only one-eighth of Russia’s population. Combined with its population decline, an aging workforce, and having to constantly adapt to a sequence of economic shocks, Russia’s unique economic geography has therefore led to a spatial pattern of development counter to what is observed in other large countries. What explains Russia’s unique economic geography and its spatial disparities? A cocktail of three factors is useful for answering this question: (i) a persistent Soviet legacy; (ii) a diverse physical geography laced with harsh climactic conditions; and (iii) a dominance of natural resources (mostly oil/gas) in peripheral regions. The Soviet legacy of a planned economy remains a burden for regions. One indicator of this persistent legacy can be seen in the ongoing socio-economic challenges facing Soviet-era industrial monotowns. Today, 319 settlements in Russia are legally identified as monotowns, with 94 classified as monotowns with a high level of socio-economic deprivation. This is despite them remaining a target of many support programs implemented by the federal government. Geography and climactic conditions do not help the situation. Russia accounts for 42 percent of the world’s land mass but its population is less than 1.9 percent of the world’s population. In addition, its extreme winter weather greatly impairs transportation services (built on continuous permafrost, Yakutsk is the coldest major city in the world, recording temperatures as low as minus 64.4°C). A sequence of shocks that hit the country over the last 25 years and the boom in the oil industry created rapid growth in peripheral, oil-rich regions. But other regions have been stymied by the persistence of structural constraints: an industrial legacy, population decline, and an aging population.